The communication strategy of the Healthy University Program and its impact on the students of the Universidad Peruana Unión - Cabrera Aquino, José Víctor (2021)
The objectives of the research were characterized by the communication strategy of the Healthy University Program of the Peruvian Union University and to determine its incidence in the change of lifestyle of the university population. A study approached from the integrative theoretical conception of one way and two way communication of social construction, analyzed by Luis Ramiro Beltrán and the strategic communication proposal of the Manual of Social Communication for Programs for the Promotion of Adolescent Health, promoted by the Pan American Organization of the Health (PAHO). Likewise, the theory of communication in health called Transtheoretical Model or Stages of Behavior Change by Prochaska and Di Clemente, will find to identify the stage achieved by the students. The study was non-experimental, cross-sectional, correlational, using a previously validated survey applied to a sample of 791 students. The results placed the students in the Action Stage, with 57.3% representing the fourth level of the five established by the theoretical model: Pre-contemplation, Contemplation, Determination, Action and Maintenance. Likewise, the main characteristic in the strategic communication of the program was the approach to an integrating vision between the Diffusionist - Unidirectional Communication Model, in which Social Marketing, Education and entertainment stand out; complemented to the Dialogic - Participative Communication Model, highlighting Social Mobilization, Media advocacy and Alternative Communication. This integration of models had an effective impact on the change in the lifestyle of the students, in which a moderate correlation was identified between the “Lifestyle” and the “Perception of the communication strategy” (R = .533), the same that was very significant (p < 0.01). In conclusion, a higher level of trustworthy perception of the Healthy University Program, a higher level reached in the Stages of healthy lifestyle behavior change.